Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the center and radius of the circle defined by the equation [tex]\( x^2 + y^2 - 6x + 10y + 25 = 0 \)[/tex], we need to rewrite the equation in the standard form of a circle's equation [tex]\((x-h)^2 + (y-k)^2 = r^2\)[/tex], where [tex]\((h,k)\)[/tex] is the center and [tex]\(r\)[/tex] is the radius.
Here are the detailed steps:
1. Rewrite the equation by grouping the [tex]\(x\)[/tex]-terms and [tex]\(y\)[/tex]-terms:
[tex]\[ x^2 - 6x + y^2 + 10y + 25 = 0 \][/tex]
2. Complete the square for the [tex]\(x\)[/tex]-terms:
[tex]\[ x^2 - 6x \quad \Rightarrow \quad x^2 - 6x + 9 - 9 \quad \Rightarrow \quad (x - 3)^2 - 9 \][/tex]
3. Complete the square for the [tex]\(y\)[/tex]-terms:
[tex]\[ y^2 + 10y \quad \Rightarrow \quad y^2 + 10y + 25 - 25 \quad \Rightarrow \quad (y + 5)^2 - 25 \][/tex]
4. Substitute back into the equation:
[tex]\[ (x - 3)^2 - 9 + (y + 5)^2 - 25 + 25 = 0 \][/tex]
5. Simplify the equation:
[tex]\[ (x - 3)^2 - 9 + (y + 5)^2 = 0 \][/tex]
[tex]\[ (x - 3)^2 + (y + 5)^2 - 9 = 0 \][/tex]
[tex]\[ (x - 3)^2 + (y + 5)^2 = 9 \][/tex]
6. Rewrite in the standard circle form [tex]\( (x - h)^2 + (y - k)^2 = r^2 \)[/tex]:
[tex]\[ (x - 3)^2 + (y + 5)^2 = 3^2 \][/tex]
From this, we can see that the center of the circle [tex]\((h, k)\)[/tex] is [tex]\((3, -5)\)[/tex] and the radius [tex]\(r\)[/tex] is 3.
Thus, the correct answer is:
[tex]\[ \boxed{A \text{. Center } (3, -5) ; \text{ radius } 3} \][/tex]
Here are the detailed steps:
1. Rewrite the equation by grouping the [tex]\(x\)[/tex]-terms and [tex]\(y\)[/tex]-terms:
[tex]\[ x^2 - 6x + y^2 + 10y + 25 = 0 \][/tex]
2. Complete the square for the [tex]\(x\)[/tex]-terms:
[tex]\[ x^2 - 6x \quad \Rightarrow \quad x^2 - 6x + 9 - 9 \quad \Rightarrow \quad (x - 3)^2 - 9 \][/tex]
3. Complete the square for the [tex]\(y\)[/tex]-terms:
[tex]\[ y^2 + 10y \quad \Rightarrow \quad y^2 + 10y + 25 - 25 \quad \Rightarrow \quad (y + 5)^2 - 25 \][/tex]
4. Substitute back into the equation:
[tex]\[ (x - 3)^2 - 9 + (y + 5)^2 - 25 + 25 = 0 \][/tex]
5. Simplify the equation:
[tex]\[ (x - 3)^2 - 9 + (y + 5)^2 = 0 \][/tex]
[tex]\[ (x - 3)^2 + (y + 5)^2 - 9 = 0 \][/tex]
[tex]\[ (x - 3)^2 + (y + 5)^2 = 9 \][/tex]
6. Rewrite in the standard circle form [tex]\( (x - h)^2 + (y - k)^2 = r^2 \)[/tex]:
[tex]\[ (x - 3)^2 + (y + 5)^2 = 3^2 \][/tex]
From this, we can see that the center of the circle [tex]\((h, k)\)[/tex] is [tex]\((3, -5)\)[/tex] and the radius [tex]\(r\)[/tex] is 3.
Thus, the correct answer is:
[tex]\[ \boxed{A \text{. Center } (3, -5) ; \text{ radius } 3} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.